2018
DOI: 10.3329/aajbb.v3i2.64788
|View full text |Cite
|
Sign up to set email alerts
|

Culture and management techniques of Vietnamese Koi

Abstract: The first time study approach about culture and management in Bangladesh was conducted to observe the induce breeding, nursing and rearing technique of Vietnam koi (Anabas testudineus) fish culture in fresh water farm in Mymensingh region, Bangladesh for a period of 120 days from May, 2013 to August, 2013. In this study, inducing agent PG was used to achieve fertilization and hatching success of climbing perch, Anabas testudineus. During induce breeding, male and female in a ratio of 1:1 were used. The females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The total annual profit from Vietnam koi culture was estimated at 128,440 (BDT/ha). In Vietnam Koi (Anabas testudineus) culture, it was reported that Food Conversion Ratio (FCR) of the supplementary feed was 1.63, the survival rate 70%, the production 167 kg/decimal and net benefit 548,455 BDT with a cost-benefit ratio of 1.43 (Faruk, 2018) [10] . Thus, monoculture of Vietnam Koi culture with supplementary feed was as economically feasible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The total annual profit from Vietnam koi culture was estimated at 128,440 (BDT/ha). In Vietnam Koi (Anabas testudineus) culture, it was reported that Food Conversion Ratio (FCR) of the supplementary feed was 1.63, the survival rate 70%, the production 167 kg/decimal and net benefit 548,455 BDT with a cost-benefit ratio of 1.43 (Faruk, 2018) [10] . Thus, monoculture of Vietnam Koi culture with supplementary feed was as economically feasible.…”
Section: Discussionmentioning
confidence: 99%
“…However, the production from aquaculture is growing faster than inland capture and marine capture fisheries. Among the cultured species, carp, catfishes and perches contributed the most production (Faruk et al, 2018) [10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation